An ontology-based integrated architecture for personalised information search and recommendation. (2016) - Besbes, Ghada; Haddad, Mohamed Ramzi; Baazaoui-Zghal, Hajer
Nowadays, web content consumers may face choice overload with regard to the huge amount of resources available on services or content providers' platforms. Moreover, the available descriptions of such goods may be complex and ambiguous which requires assisting users while exploring the available content and finding the right resources with regard to each individual's personal needs and tastes. Such challenges are tackled mainly by personalisation and recommendation approaches. In this paper, we present a hybrid context-aware personalisation architecture integrating an information search and a recommendation approach. The main objective here is to facilitate the access to relevant content depending on users' contextual objectives and needs. The proposed architecture was evaluated on the INEX 2013 Social Book Search collection whose main challenge is to satisfy users' requests with the most interesting books.